PENGARUH PROSES PEREBUSAN TERHADAP KADAR PROTEIN YANG TERKANDUNG DALAM TAUGE BIJI KACANG HIJAU (Phaseolus Radiatus) - Anita Agustina; Desi Rahmawati (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2016)
Protein is an important or main component of animal and human cells. The source of vegetable protein can be obtained from soybeans and other legumes, as well as their processed results. This component can be denatured due to changes in temperature, pH, heavy metal ions, mechanical movement, alcohol, acetone, ether, and detergent. The main aim of this study was to determine the effect of boiling on protein in the seeds of mung beans. The samples were analyzed using the Lowry method. The result of quantitative test showed that the average level of protein in the samples before boiled was 1.664% w/w, while after boiled was 0632% w/w. The statistical test showed that t-score of the sample was 43.827 and t-table was 2.920, and p-score was 0.001. Of the results of the study, it can be concluded that there is a significantly difference between the levels of protein before and after boiled. Boiling gives effect to the protein levels in the samples.